PEMBERDAYAAN MASYARAKAT NELAYAN DI WILAYAH PESISIR KELURAHAN KOLO KECAMATAN ASAKOTA KOTA BIMA PROVINSI NTB - Arisman Arisman; Ihsan Ihsan; Kasmawati Kasmawati (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
The Study on Empowerment of Fishermen Communities in the Coastal Area of Kolo Village, Asakota District, Bima City, NTB Province. Supervised by Ihsan as the first mentor and Kasmawati as the second mentor.This study aims to determine: 1) the economic, social and cultural conditions of the fishing community in the coastal area of the Kolo Village 2) the factors that influence the empowerment of the fishing community in the coastal area of the Kolo Village 3) the strategy for empowering the fishing community in the coastal area of the Kolo Village The data collection method used in this research is by using primary data and secondary data. The process of obtaining primary data is carried out through interview techniques and direct observation in the field, then secondary data is obtained through the relevant agencies, in this case the Department of Marine Affairs and Fisheries, the Department of Tourism. conducting data analysis is determining the stages of activity against the data that is being and has been collected with the aim of drawing conclusions. the economic condition of the community still needs to be improved specifically to increase the income and standard of living of the fishing community. while the socio-cultural aspects of society are open. The factor that influence the empowerment of fishing communities in the coastal area of Kolo Village are fishing business. The results of the matrix analysis of the relationship between SWOT elements for community empowerment strategies show 2 (two) priority alternative strategies, namely 1) technology development and fisheries scale businesses 2) increasing fishing productivity using environmentally friendly fishing gear